Hepatobiliary fascioliasis: A neglected tropical disease - Patel, Kinjal P; Shah, Anand; Shetty, Anjali; Rodrigues, Camilla (Indian Journal of Case Reports, 2019)
Human fascioliasis is a zoonotic disease caused by two parasites of class Trematoda, namely Fasciola hepatica and F. gigantica. It is prevalent, particularly in regions with farming communities having sheep or cattle. In India, cases are not frequently reported despite being one of the dominant countries in livestock production. Usually, humans are incidental hosts that acquire infection by ingesting contaminated aquatic vegetation or water. If not diagnosed timely, it can lead to fatal complications.The authors report a case of hepatobiliary fascioliasis in a female presented with non-specific complaints. A thorough investigation including parasitological evaluation helped to reach the diagnosis. This case highlights the importance of awareness, diagnosis and appropriate treatment of  fascioliasis with Triclabendazole for complete cure.